Ruang Publik Sebagai Arena Media Ekspresi Seni Grafis Teknik Hardboard Cut - Dwi Wahyuni Hamka; Faidhul Inayah (Nuansa Journal of Arts and Design, 2022)
The public as the media the expression of the technique of hardboard cut in Yogyakarta. The study aims to reveal how the public selected an artist’s graphical conventional, especially the technique of hardboard cut as the media for the expression of artists in the expression it. The basis of the theory be used is the theory of hegemony culture by Antonio Gramsci. The research said that the work of hardboard cut techniques of graphics art used as media propaganda to the realization of intellectual society through the nuptial chamber work on the public are still less effective in this case can give the realization, it can affect people or less effective in an attempt to break the hegemony of intellectual society. Although int the other side it understood and agree it was very like the poster shown criticizing the government which is in accord with what that would ta take the society and general.